THE INFLUENCE OF SELF-EFFICACY ON EMPLOYEES' CAREER PLANNING WITH CAREER MOTIVATION AS A MEDIATION VARIABLE IN THE MEDANG DERAS DISTRICT OFFICE OF BATU BARA DISTRICT: PENGARUH EFIKASI DIRI TERHADAP PERENCANAAN KARIR PEGAWAI DENGAN MOTIVASI KARIR SEBAGAI VARIABEL MEDIASI PADA KANTOR CAMAT MEDANG DERAS KABUPATEN BATU BARA - Pradito , Okto (UPMI Proceeding Series, 2023)
The purpose of this study was to analyze: (1) The effect of efficacy on employee career planning at the Medang Deras sub-district office, Batu Bara Regency. (2) the effect of self-efficacy on employee career motivation at the Medang Deras sub-district office, Batu Bara Regency. (3) the Effect of Career Motivation on Employee Career Planning at the Medang Deras Subdistrict Office, Batu Bara Regency. (4) Self-Efficacy Influences on Employee Career Planning through Career Motivation Mediation at the Medang Deras Sub-district Office, Batu Bara Regency with a sample of 34 people. using 20 measuring instrumen. The results of this study indicate that efficacy has a significant effect on employee career palanning with a t value 2.870, t table of 2.036, self-efficacy has a significant effect on career motivation with a t-count value of 2.093 t table of 2.036, career motivation has no significant effect on employee career planning with a t-count value of 0.182 t-table of 2.036, career motivation significantly does not mediate the influence between self-efficacy and career planning employees with a t-count value of 0.163 t-table of 2.036.